Desde la subjetividad de familias cubanas migrantes: experiencias de la COVID-19. / From the subjectivity of Cuban migrant families: experiences of COVID- 19. - Consuelo Martín Fernández; Jany Barcenas Alfonso; Claudia Cancio Bello Ayes (Universidad de La Habana, 2020)
As part of the psychological counseling service at a distance during COVID-19-Psicogrupos WhatsApp- the Family and Migration Group was created to assist migrant Cuban families in this new context. This article presents the authors' experience during seven months of work (March to October 2020), in the role of coordinators of 50 group sessions. It describes the main issues that Cuban families with migrant ties affront, associated with the effects of the current situation and its psychological consequences. Likewise, we explain the subjective transformations evidenced in the group development, from the articulation of different and complex psychological process. The group recognizes the training and implementation of responsible self-care by migrant families as an indispensable learning during this time. The social connotations of some types of ties between migrant Cuban families during COVID-19, are identified; ties marked by family history and dynamic, now re-dimensioned or tinted according to the circumstances, expectations, the possibility of reflection, and a healthy communication. In this sense, three dimensions are analyzed: affective distance, conflict, and the dynamic of the familiar bonds, that inform the social connotations of rejection or acceptance of the migration during the pandemic. Finally, conclusive reflections are shared about identified learnings in migrant family ties, and from them, as recommendations, actions are suggested for institutional and government management for the treatment of this sensitive topic. / RESUMEN Como parte del servicio de orientación psicológica a distancia Psicogrupos WhatsApp durante la COVID-19, se creó el grupo Familia y Migraciones para la atención a familias cubanas migrantes en este nuevo contexto. Este artículo presenta la experiencia de siete meses de trabajo (marzo-octubre, 2020) de las autoras, en el rol de coordinadoras de 50 sesiones grupales. Se describen las principales problemáticas que afrontan familias cubanas con vínculos migratorios, asociadas a los efectos de la situación actual y las consecuencias psicológicas. Asimismo, se explican las transformaciones subjetivas evidenciadas en el desarrollo del grupo, a partir de la articulación de diferentes y complejos procesos psicológicos. El grupo reconoce la enseñanza y puesta en práctica del autocuidado responsable en las familias migrantes como un aprendizaje imprescindible durante este tiempo. Se identifica la connotación social de algunos tipos de vínculos entre familias cubanas migrantes durante la COVID-19. Vínculos marcados por las historias y dinámicas familiares, ahora redimensionadas o matizadas en función de las circunstancias, las expectativas, la posibilidad de la reflexión y la comunicación saludable. En este sentido se analizan tres dimensiones: distancia afectiva, conflictividad y dinámica del vínculo familiar, que cualifican la connotación social de rechazo o aceptación de la migración durante la pandemia. Finalmente, se comparten reflexiones conclusivas sobre los aprendizajes identificados en los vínculos con familias migrantes y a partir de estos, a modo de recomendaciones, se sugieren acciones para la gestión de instituciones y gobierno respecto al tratamiento de esta sensible temática.